THE IMPACT OF CURRENCY CLAUSE AND EXCHANGE RATE ON SERBIAN ECONOMY - Popov, Đorđe (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
In nineties Serbia survived the disintegration of the former Yugoslavia, intense UN sanctions, and 1999 78 days of bombing by NATO. This has resulted in a drop in production and hyperinflation. The confidence in the national currency the dinar has been lost. In order to do business in Serbia returned to normal framework the Law on Foreign Exchange imposed the possibility of nomination the loans in foreign currencies. This prompted the business, but it meant a de facto legalization of dual currency system. The logical consequence was the high degree of dollarization. It is important to mention that the dual currency system limited the possibilities of monetary policy of the National Bank of Serbia. Dollarization after the first positive results showed their expected bad sides. Appreciation of the dinar was one of the consequences. The trade deficit and foreign debt grew. Due to the appreciation production rate remained at 40% of its 1989 level, and unemployment has risen to 27%. The benefit of the appreciation had only importers and foreign-owned banks. They take out the capital abroad. Therefore, it is necessary to make changes to the Foreign Exchange Law and abolish foreign currency clause at least for a new loans. It should be recalled that the Supreme Court of Iceland declared the nominations of loans in foreign currency as illegally.